“This is just to say” parody / Syedda Fareeha Hussain Syed Mohd Javed Hussain - Syed Mohd Javed Hussain, Syedda Fareeha Hussain (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.